2007
DOI: 10.1021/bi7008773
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic and Cation−π Interactions Enhance Helix−Helix Association in a Membrane Environment

Abstract: The cation-pi interaction is an electrostatic attraction between a positive charge and the conjugated pi electrons of an aromatic ring. These interactions are well documented in soluble proteins and can be both structurally and functionally important. Catalyzed by observations in our laboratory that an Ala- and Ile-rich two-helix transmembrane segment tended to form SDS-resistant dimers upon the incorporation of suitably located Trp residues, here we have constructed a library of related constructs to study sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 49 publications
3
69
0
Order By: Relevance
“…Moreover, the presence of a phenylalanine in addition to the GXXXG motif enhances the self-association of the GpA TMD (8). Several other reports have confirmed that aromatic residues, either alone or near the GXXXG motif, can stabilize the TMD helix dimerization of membrane proteins (8,29,30 ). Therefore, we speculated that, as in the other studied receptors, phenylalanine might be involved in regulating the interaction strength of the syndecan TMDs.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, the presence of a phenylalanine in addition to the GXXXG motif enhances the self-association of the GpA TMD (8). Several other reports have confirmed that aromatic residues, either alone or near the GXXXG motif, can stabilize the TMD helix dimerization of membrane proteins (8,29,30 ). Therefore, we speculated that, as in the other studied receptors, phenylalanine might be involved in regulating the interaction strength of the syndecan TMDs.…”
Section: Discussionmentioning
confidence: 85%
“…To identify the TM residues involved in CD16A association with adaptor modules, a panel of mutants was prepared in three blocks of three mutations. Based on the documented roles of polar and aromatic residues in driving TM helix associations (17,18), we mutated these amino acid types in the CD16A TM sequence ( Fig. 2A) to alanine and evaluated the association of mutants with each signaling molecule using the IVT system described above.…”
Section: Cd16amentioning
confidence: 99%
“…Thus, they represent a versatile instrument for interactions between transmembrane helices. Several studies suggest that Phe, Trp and Tyr facilitate helix-helix association in transmembrane domains [82][83][84]. When placed in position i-3 of a GXXXG motif, Phe can enhance transmembrane domain interactions in model peptides derived from library screening [82].…”
Section: Aromatic Interactionsmentioning
confidence: 99%